ANALISIS KINERJA KEUANGAN BERDASARKAN KONSEP VALUE FOR MONEY (Studi di Kantor Camat Taliwang Kabupaten Sumbawa Barat) - I Nyoman Sutama; Fani Fatona; Nining Sudiyarti (Fakultas Ekonomi dan Manajemen, 2022)
The purpose of this study was to determine the level of financial performance based on the concept of Value For Money in the Taliwang District Office, West Sumbawa Regency. This type of research is descriptive quantitative, namely research that aims to provide an overview of phenomena or symptoms in society by using numbers. The type of data used is secondary data in the form of an annual report at the Taliwang District Office, West Sumbawa Regency. The analytical tool used in this study is the concept of value for money, including economic ratios, efficiency ratios and effectiveness ratios. The results of the study show that the financial performance of the Taliwang Sub-District Office of West Sumbawa Regency in 2020-2021 is in the criteria of being uneconomical with the achieved ratio level being above 105%, and inefficient with the achieved ratio level being above 100%. Meanwhile, the effectiveness criteria are in the effective category with a ratio between 90% -100%. Based on these results, it is necessary to review the budget used by carrying out a strict controlling system for the budget issued by budget users. The Taliwang sub-district office of West Sumbawa Regency as a budget user must use the budget as economically as possible, minimize waste and unproductive expenses such as purchasing employee computers that are damaged, because they can still be repaired, and use the budget as effectively as possible to achieve the goals set.